Enhancing the database of OTRmail extension for thunderbird - Zheng, Kaizhong. (2011)
The Internet in the 21st century has become an indispensable part of our lives and this has led to the proliferation of Electronic mail (Email). Despite its conveniences, Email faces several problems such as security issues and this has been addressed by various Email security solutions. However, these solutions use long-lived encryption keys, which limit their usage. Arising from the need to overcome this limitation is the OTRmail. This Email security solution is based on the concept of Off-The-Record (OTR) which introduces the idea of perfect forward secrecy, repudiability and the usage of short-lived secret key.Although a raw version of the OTRmail engine has been developed, much work is required to improve it, especially its database system. This is due to the introduction of new features for its users in the OTRmail which requires the storage and retrieval of new key attributes. Thus, the focus of this project is to improve the OTRmail’s database by researching on suitable database systems, developing the chosen system, integrating it into OTRmail and the development of the User Interface (UI) to gather user’s inputs.